2021
DOI: 10.3390/jcm10122677
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Preoperative Video Head Impulse Test to Predict the Nerve of Origin in Patients with Vestibular Schwannomas

Abstract: Vestibular schwannoma (VS) originates from Schwann cells in the superior or inferior vestibular nerve. Identifying the precise origin will help in determining the optimal surgical approach. We retrospectively analyzed the preoperative vestibular function test according to VS origin to determine whether the test is a valuable indicator of tumor origin. Forty-seven patients with VS (male:female = 18:29, mean age: 54.06 ± 13.50 years) underwent the cochleovestibular function test (pure-tone audiometry, caloric te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Additionally, they reported that low posterior canal gain had a specificity of 94.4% for predicting the hearing prognosis. Also, attempts were made to discriminate the origin of the vestibular schwannoma based on the PC gain analysis (25), and another study report that the AC gain is relatively preserved compared with the PC and HC gain in the central acute vestibular syndrome (21). These results suggest that the function of the vertical canal often has various clinical implications although vertical canal vHIT required technical proficiency and has lower reliability compared with HC testing.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they reported that low posterior canal gain had a specificity of 94.4% for predicting the hearing prognosis. Also, attempts were made to discriminate the origin of the vestibular schwannoma based on the PC gain analysis (25), and another study report that the AC gain is relatively preserved compared with the PC and HC gain in the central acute vestibular syndrome (21). These results suggest that the function of the vertical canal often has various clinical implications although vertical canal vHIT required technical proficiency and has lower reliability compared with HC testing.…”
Section: Discussionmentioning
confidence: 99%